Efektivitas Cat Reflektif Surya BeCool terhadap Penurunan Suhu Ruang pada Atap Spandek di Mushola Al Anshor: The Effectiveness of BeCool Solar Reflective Paint in Reducing Room Temperature on Spandek Roofs in Al Anshor Prayer Room - Nursilawati, Nadya; Rahmawati, Novi; Octaviani, Indri; Affriani, Asri Ria (Elektriese: Jurnal Sains dan Teknologi Elektro, 2026)
Air temperature significantly affects comfort and quality of life. Rising air temperatures due to climate change significantly affect indoor thermal conditions, especially on spandek roofs with high thermal conductivity. These conditions reduce comfort and increase cooling energy requirements. Therefore, innovation is needed to reduce air temperature while using minimal energy. One such innovation is coating the roof surface with a reflective paint that reduces solar heat gain. This study aims to analyze the effectiveness of solar-reflective paint in reducing room temperatures in spandek-roofed buildings. The method used is an experiment. The stages include measuring the temperature before and after coating the roof with solar reflective paint. The tool used is an Elitech RC-4 logger installed at three strategic points in the building: on the surface, beneath the surface, and on the roof ceiling. The results showed that applying solar-reflective paint reduced the average room temperature by 2.84 °C, from 33.69 °C to 30.85 °C. The largest decrease occurred on the roof surface, by 4.22°C, from 33.69°C to 30.85°C. These findings confirm that solar-reflective paint can be an effective solution for lowering indoor temperatures, thereby improving thermal comfort, reducing heat loads, and supporting energy conservation initiatives.